Web-Based Financial Information System at Micro Enterprise D'Elixir Bracelet - Vaizal Asy’ari; Ludmina Elfrida Beka Putri; Evi Pungky Febriani; Nanik Kustiningsih; Wan Adibah Wan Ismail; Pompong Budi Setiadi (CV ODIS, 2022)
The purpose of this study is to find out the process of processing financial data in the form of financial entry and expenditure transactions on Micro Enterprise D'Elixir Bracelet in order to find out the problems that occur in the monitoring process and to examine the results of the design and manufacture of financial information systems on Micro Enterprise D'Elixir Bracelet. The Financial Information System at Micro Enterprise D'Elixir Bracelet is still done manually, utilizing the Microsoft Excel application for recording financial transactions and saving transaction evidence (invoices, receipts, notes, receipts, or other evidence) on the folder manually. This makes it difficult to record, process, and search for past election results. For this reason, an application is needed that can facilitate the recording of financial transactions, storage of transaction evidence, as well as knowing the current financial position. This web-based application is designed to accommodate financial income and expenditure transactions according to their category. In this research, we used descriptive qualitative and making this web-based Financial Information System the writer makes use of the SDLC (Software Development Cycle) design method and runs the application the usage of localhost XAMPP. The Financial Information System at Micro Enterprise D'Elixir Bracelet Financial Information System can provide convenience in managing financial transactions, reduce paper usage, and use time more quickly and accurately. The end result of this final project is a web-based financial information system give a good impact on business in the Micro Enterprise D’Elixir Bracelet.